Beyond Compliance: A Qualitative Meta-Synthesis of Public Service Motivation, Ethical Behavior, and Employee Performance in Public Organizations - Tunggul Prasodjo (Golden Ratio of Social Science and Education, 2026)
This systematic literature review employs a qualitative meta-synthesis approach to examine the interconnected relationships between Public Service Motivation (PSM), ethical behavior, and employee performance within public organizations. Drawing from 64 peer-reviewed articles published between 2019 and 2026, sourced from Scopus, Web of Science, ScienceDirect, Emerald Insight, SpringerLink, and SAGE Journals, this study synthesizes empirical findings to develop an integrated conceptual framework. The analysis reveals five major themes: (1) PSM as a moral foundation of public employees; (2) ethical behavior as a mediating mechanism between motivation and performance; (3) employee performance beyond administrative compliance; (4) organizational climate and ethical leadership as contextual moderators; and (5) tensions between bureaucratic compliance and public values. The findings demonstrate that PSM serves as an intrinsic motivational foundation that shapes prosocial orientations, which are subsequently translated into meaningful performance outcomes through ethical behavior. Organizational contextual factors particularly ethical leadership and organizational climate significantly moderate these relationships. This review contributes theoretically by integrating PSM theory, social exchange theory, ethical leadership theory, and institutional theory into a unified framework. Practical implications suggest that public organizations should move beyond compliance-based governance toward value-based governance that emphasizes integrity, ethical leadership cultivation, and intrinsic motivation development to enhance public service quality.